2021
DOI: 10.2147/rmhp.s289943
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference is Associated with Short-Term Outcomes in Non-Surgically Managed Acute Aortic Dissection Patients with Hypertension: A Retrospective Cohort Study

Abstract: Background The management of acute aortic dissection (AAD) has improved; however, the outcomes related to different gender with short-term outcomes in non-surgically managed AAD with hypertension are still limited. Our objective was to explore gender-differences in association with short-term outcomes of patients comorbid with hypertension in non-surgically managed AAD. Methods This is an observational retrospective single-center cohort. We analyzed the data from the Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is important to take into consideration preoperative and postoperative risk factors, and the gender gap to improve aortic dissection management and decrease their impact on the outcome [ 7 , 25 ]. A focus on eligible risk factors is critical in emergency cases and their identification and good management might influence the mortality rates [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to take into consideration preoperative and postoperative risk factors, and the gender gap to improve aortic dissection management and decrease their impact on the outcome [ 7 , 25 ]. A focus on eligible risk factors is critical in emergency cases and their identification and good management might influence the mortality rates [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inotropic and vasoconstrictor drugs, typically utilized preoperatively for persistent hypotension and postoperatively to manage vasoplegia associated with a systemic inflammatory syndrome, are related to renal dysfunction in aortic dissection, particularly in female patients [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Sex differences in mortality among aortic dissection patients have gained attention, 2 however, data pertaining to disparities in outcomes between males and females are conflicting. 3 While some studies have demonstrated that surgically treated females with ATAAD have a higher odds of in-hospital mortality compared with males, 4 , 5 , 6 , 7 , 8 other studies have found no significant differences in in-hospital mortality between males and females after surgical repair of ATAAD. 9 , 10 , 11 , 12 A systematic review and meta-analysis reported no difference in early mortality between sexes after surgical repair of ATAAD.…”
mentioning
confidence: 98%